Spatial variation in modelled hydrodynamic characteristics associated with valley confinement in the Krom River wetland: implications for the initiation of erosional gullies - Schlegel, Philippa Kirsten (Rhodes University, Faculty of Science, Department of Geography, 2018)
Gully erosion is a significant and widespread feature of southern African wetlands, including the wetlands of the Krom River, Eastern Cape. Gully erosion in wetlands is consistently being viewed as a major contributing factor to wetland degradation and eventual collapse. Many gullies exist in the Krom River and Working for Wetlands has spent large sums of money to stabilise head-cuts with the expectation that further erosion would be halted and possibly avoided altogether. Observations in the Krom River wetlands have revealed that most gullies in the wetland are initiated where the width of the trunk valley has been reduced as a consequence of deposition by tributary alluvial fans that impinge on the trunk valley and reduce its width. The aim of this study was to examine variation in hydrodynamic characteristics for a range of discharges, as flow in the broad Kompanjiesdrif basin (~250 meters wide) is confined in a downstream direction to a width of less than 50 meters by a combination of a large impinging left bank tributary alluvial fan that coincides with a resistant bedrock lithology. The study was done by collecting topographical survey data using a Differential Global Positioning System in order to create a Digital Terrain Model with a suitable resolution. Flow was recorded using a Marsh-McBirney Model 2000 Flo-Mate as well as recording the flood extent for each flow condition; this was used in the calibration process of the model. Vegetation measurements were conducted in order to calculate a roughness value across the valley floor. A two-dimensional raster based flood inundation model, CAESAR-Lisflood and a one-dimensional hydraulic analysis model, HEC-RAS, were then used to simulate different parameters associated with variation in discharge, including flow velocity, water depth and stream power, thereby creating a better understanding of the hydraulic characteristics that may promote the formation of gullies in the wetland. Based on these hydraulic analyses it is evident that the effect of impinging alluvial fans on hydraulic characteristics such as flow velocity, water depth and stream power, may lead to the initiation of gullies within the Krom River wetland. This work improves understanding of the collapse of palmiet wetlands in steep-sided valleys within the Cape Fold Mountains of South Africa, and can aid in wetland management.
Keywords: Soil erosion -- South Africa -- Eastern Cape; Wetland management -- South Africa -- Kromme River (Eastern Cape); Wetland conservation -- South Africa -- Kromme River (Eastern Cape)